Sulforaphane ameliorates non-alcoholic steatohepatitis by KLF4-mediated macrophage M2 polarization - Xianghui Huang; Jia Xu; Ye Xu; Bingxin Huangfu; Feng Zhang; Yanzhou Hu; Ruxin Gao; Xinxin Ren; Boyang Zhang; Kunlun Huang; Xiaoyun He (Food Science and Human Wellness)
Non-alcoholic fatty liver disease (NAFLD) has become a global issue and a severe threat to public health. However, to date, no approved therapeutic drugs have been developed. Dietary interventions with natural products have shown promise in preventing and treating NAFLD. Sulforaphane (SFN) is a phytocompound with antioxidant and anti-inflammatory properties, and previous research has demonstrated that SFN can ameliorate hepatic lipid accumulation and inflammation. However, the molecular mechanisms underlying these beneficial effects remain unclear. In this study, we confirmed the protective effects of SFN on excessive lipid accumulation and inflammatory injury in a high-fat, high-fructose diet-induced non-alcoholic steatohepatitis (NASH) mouse model. We found that SFN attenuates the inflammatory injury in a macrophage cell line and the liver of NASH mice, owing to the promotion of M1-type macrophage polarization toward the M2-type and the regulation of inflammatory mediators. Further analysis demonstrated that this SFN-induced macrophage M2-type polarization occurs in a Krüppel-like factor 4 (KLF4)-dependent manner. In summary, we uncovered a new mechanism of action underlying SFN activity and provide evidence that dietary intervention with SFN might be protective against NASH.